The Significance of the Ocular Adverse Effect Induced by Systemic Taxane Application - Ya-Ting Ye; Zi-Yi Zhou; Li-Shi Wen; Yu Sun; Zhao-Jie Chu; Guo-Rui Dou (Frontiers in Bioscience-Landmark, 2022)
In recent years, in-depth research on anti-tumor therapy has brought the emergence of new active chemotherapeutic agents and combination regimens. However, as one of them, taxane drugs are widely used in clinical practice, but it should be noted that many side reactions caused by their application bring some difficulties to routine management. Among the side reactions related to taxane anti-tumor therapy, ocular adverse reactions are occasionally reported and are not life-threatening but may seriously affect patients’ life quality. Thus, the continuation, reduction and cessation of taxane chemotherapy still need to be further evaluated by ophthalmologists and oncologists once the side effects show up. To prevent ocular side reactions, close attention should be paid to complications during medication. To facilitate the oncology department and ophthalmologists to comprehensively understand the ophthalmic adverse reactions of taxane drugs and their possible mechanisms and improve drug use efficiency, we collected relevant literature and reviewed and provided some suggestions for the monitoring and managing of ophthalmic toxicity.